Formation of a Low-Density Liquid Phase during the Dissociation of Gas Hydrates in Confined Environments - Lihua Wan; Xiaoya Zang; Juan Fu; Xuebing Zhou; Jingsheng Lu; Jinan Guan; Deqing Liang (Nanomaterials, 2021)
The large amounts of natural gas in a dense solid phase stored in the confined environment of porous materials have become a new, potential method for storing and transporting natural gas. However, there is no experimental evidence to accurately determine the phase state of water during nanoscale gas hydrate dissociation. The results on the dissociation behavior of methane hydrates confined in a nanosilica gel and the contained water phase state during hydrate dissociation at temperatures below the ice point and under atmospheric pressure are presented. Fourier transform infrared spectroscopy (FTIR) and powder X-ray diffraction (PXRD) were used to trace the dissociation of confined methane hydrate synthesized from pore water confined inside the nanosilica gel. The characterization of the confined methane hydrate was also analyzed by PXRD. It was found that the confined methane hydrates dissociated into ultra viscous low-density liquid water (LDL) and methane gas. The results showed that the mechanism of confined methane hydrate dissociation at temperatures below the ice point depended on the phase state of water during hydrate dissociation.